Kykladitisses: agnōstes istoreis gynaikōn tōn Kykladōn = (kykladitisses) : untold stories of women in the Cyclades - Athanasulēs, Dēmētrēs; Iossif, Panagiotis P.; Phappas, Iōannēs (Museio Kykladikēs Technēs, 2025)
"A Greek English bilingual catalogue published as part of the new series of archaeological exhibitions organized by the Museum of Cycladic Art called "Human Histories" for the exhibition "Kykladitisses: Untold stories of women in the Cyclades". The catalogue presents the transformations and the multiple roles of women that have defined the history of the Archipelago through time highlighting their importance at a time when women continue to assert their independence and respect for their specificity within the modern community, the free choice of the roles that express each of them and their liberation from stereotypes that survive in the common consciousness despite the long struggles of past centuries. The catalogue is divided into two volumes. The first volume contains 520 pages in which all the artefacts in the exhibition are illustrated in each section in extremely high quality and resolution photographs, together with a brief explanation giving all the details of their identity. The long introductory text explaining the concept of the exhibition and the sections is written by the two curators of the exhibition, and the volume concludes with five essays by leading female scholars of Cycladic culture through time.The detailed scientific documentation and publication of each object in extensive essays is included in the second volume of the catalogue"--Publisher's website
Zweisprachiger Katalog zu einer archäologischen Ausstellung im Museum für Kykladische Kunst, Athen, Griechenland, 12. Dezember 2024 - 4. Mai 2025
Keywords: Cyclades (Greece) -- Exhibitions; Cyclades (Grèce) - Expositions; Ausstellungskatalog -- Museio Kykladikēs Technēs -- 12.12.2024-04.05.2025 -- Athen